Sistem Pendaftaran Online Menggunakan Model Fast Berbasis Web - Wijaya, Benny; Rachmatsyah, Agus Dendi; Yanuarti, Elly; Irawadi, Syafrul (LPPM STIKOM Tunas Bangsa, 2023)
Alfatih Education Institute is a non-formal tutoring educational institution, Alfatih is one way for students to improve their ability to learn and obtain additional education. Currently, Alfatih still uses manual methods in terms of the registration process and data recording, this manual system also results in the registration process tending to be slow because the data of new students who have registered have not been integrated and is not managed properly, because they still use archives in physical form that are vulnerable to damage or even loss. Along with the development and advancement of computer technology, everything began to switch to equipment that uses computerized systems. So do not be surprised if slowly computerized systems are applied in the world of education. To be able to overcome these problems, a builder and design of a new tutoring participant registration information system was made at the Alfatih Education Institute. The method used is the Fats model with an object-oriented system approach modeled using UML. The end result of the design and development of information systems is the existence of an application that can provide easy access to information and the registration process so that the administrative process of new student admissions becomes more effective and efficient.